Morphometric Characterization and Phenotypic Diversity of PE Goats as Local Animal Genetic Resources in Banyumas, Indonesia - Mulyoto Pangestu; Doso Sarwanto; Sari Tuswati; Wida Nurnaningsih (Journal of Sustainable Livestock, 2026)
The Etawah Crossbred (PE) goat is a vital local genetic resource in Indonesia, yet the lack of comprehensive phenotypic data hampers sustainable breeding and conservation efforts. This study aimed to characterize the morphometric and phenotypic diversity of PE goats in the Pekuncen area of Banyumas to support genetic resource inventory and local biodiversity policies. Using a descriptive cross-sectional design and purposive sampling, quantitative and qualitative data were systematically collected from 150 male and female goats aged six months and older. Data analyses utilized descriptive statistics, ANOVA, Principal Component Analysis (PCA), and hierarchical clustering. The results revealed moderate to high variability in key traits, specifically shoulder height (mean 65.3 cm) and chest circumference (mean 72.5 cm), which demonstrated a strong positive correlation (r=0.78). These morphometric variations were significantly influenced by location, sex, and age. Furthermore, PCA and cluster analysis categorized the population into three distinct phenotypic clusters large, medium, and small individuals that explain approximately 75% of the total variance, reflecting ecological adaptation to extreme environments while retaining unique local traits. Ultimately, these findings provide a robust scientific foundation for demographically targeted conservation strategies, establishing gene banks, and advancing sustainable breeding programs for local animal genetic resources.